Navigating The Challenges and Best Practices in Sustainable Livestock Production - Zayadi, Rabiatul Adawiyah (Journal of Techno-Social, 2026)
The livestock sector needs to catch up with the exigency to multiply production in meeting the demand from growing population. With the increasingly scarce natural resources and immense release of pollutants into the environment, there is a need for the industry players to try their best in implementing sustainable livestock practices not only to ensure food security, but also to safeguard the natural resources and reduce the environmental impacts. This paper reviews the challenges faced by the livestock sector, the need for sustainable livestock production, and the best green practices that can be adopted in livestock production to ensure sustainable operation. The challenges in livestock production including food security, resource management, waste management, public health, and greenhouse gas (GHG) emission call for sustainable practices to balance between the need for intensification and the environmental impacts. The green practices on waste management, water management and circular economy approaches are also outlined. Adopting sustainable practices within the livestock sector is imperative not only for addressing the growing food demand, but also for ensuring environmental sustainability.